PENGARUH KECERDASAN EMOSI, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Universitas Islam Kalimantan M A B Banjarmasin) - Teguh Wicaksono; Muhammad Alfani; Kurniaty kurniaty (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
The Problems who discussed in this research are : 1). How the influence emotional intelligence of employee performance, 2). How the influence competence of employee performance, 3). How the influence environment work of employee performance, 4). How the influence are emotional intelligence, competence, and environment work together of employee performance. The type of research is explanatory research that is assosiative, which aims to know the relationship between two or more variables. This research conducted in Islamic University Kalimantan (Uniska) Muhammad Arsyad Al Banjary Banjarmasin. The population of this research are employes of Islamic University Kalimantan (Uniska) Muhammad Arsyad Al Banjary Banjarmasin which amounts 163 people. The method of taking data is by using a questionnaire as a source of primary data and documentation as a source of secondary data. The techniques of data analysis in this research is by using multiple regression analysis. That result of research find all hypothesis in this research already to proven significantly. The emotional intelligence weigh in significantly of employee performance. The competence weigh significantly of employee performance with magnitude of correlation. The environment work weigh in significantly of employee performance with magnitude correlation. The emotional intelligence, competence, and the environment work in simultane weigh significantly of employee performance. The implication of this research are emotional intelligence, competence, and environment work have the same role important either individually or jointly in improve of employee performance. Key word : emotional intelligence, competence, environtment work, and employee performance.